HUBUNGAN MOTIVASI KERJA PETANI DENGAN KINERJA PETANI PADI SAWAH DI DESA IWOIKONDO KECAMATAN LOEA KABUPATEN KOLAKA TIMUR - Syaiful, Syaiful; Sidu, Dasmin; Mardin, Mardin (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The objective of this study is to ascertain the correlation between farmers' work motivation and their performance in Iwoikondo Village, Loea District, East Kolaka Regency. The population of this study comprised all rice farmers residing in Iswaikondo Village, Loea District, East Kolaka Regency. It is noteworthy that the population of farmers in Iswaikondo Village, Loea Subdistrict, is comprised of nine farmer groups, with each group consisting of 25 farmers, thereby yielding a total of 225 rice farmers. The sample size was determined using the Slovin formula with a margin of error of 15%, resulting in a sample size of 38 respondents. The research sample was obtained through the implementation of the proportional random sampling method. The research variables of interest were the level of motivation and the level of performance of rice farmers. The research data collected was then subjected to quantitative descriptive analysis. The results of the study indicate that the motivations of farmers in Iwoikondo Village vary, ranging from fulfilling basic needs and security of farming to social needs through farmer groups and government support. Some farmers seek recognition for their work, while others have achieved self-actualization by focusing on innovation, sustainable agriculture, and farmer regeneration. Overall, there has been a shift in motivation from basic needs to higher achievements. Farmers' performance in Iwoikondo Village varies in terms of productivity, work quality (use of seeds), and work effectiveness. Some have not yet reached production standards, while others have met or exceeded them. Most have begun to switch to high-quality seeds, though some still use local seeds. In terms of effectiveness, only a few follow the schedule on time, with the most delays occurring during harvest. To improve performance, planning, education, and better technological and agricultural management support are needed. There is a strong and significant correlation between farmers' motivation levels and their performance, with a correlation coefficient of 0.639.